The effect of brown seaweed and polyphenol supplementation in male rabbits on the blood profile and antioxidant markers - N Knizatova; M Massanyi; R Rossi; L Ondruska; A Kovacik; K Tokarova; A Gren; G Formicki; L Binkowski; M Halo; N Lukac; P Massanyi; et al. (Veterinární Medicína, 2022)
Corrigendum in: Vet Med-Czech. 2023 Jan 19;68(1):43. doi: 10.17221/4/2023-VETMEDCurrently, in animal nutrition, the replacement of synthetic substances with natural ones was expected to improve animal health. The aim of the present study was to evaluate the effects of a dietary brown seaweed and plant polyphenol mixture in adult male rabbits on the haematological profile and antioxidant markers. Twenty-four adult male rabbits were divided into three experimental groups receiving a control diet (C) or diets supplemented with 0.3% (T1) and 0.6% (T2) of a feed additive containing brown seaweed (Laminaria spp.) and plant extracts of seaweed origin. The trial lasted for 90 days. A lower potassium concentration was observed at 30 days in the T2 group, compared with the T1 and C groups. An increase in the antioxidant status was observed (P < 0.05) from day 60 of the trial in the rabbits fed diets with an algae-polyphenolic supplement (T1 and T2 groups). Concluding, the diet supplementation of brown seaweed and polyphenol stimulates the antioxidant status of the blood, however, it does not affect the haematological profile.